2011
DOI: 10.2478/v10011-011-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Blood Antioxidant Capacity in Men and Women

Abstract: Kratak sadr`aj: Cilj studije bio je da se odredi antioksidantni kapacitet u krvi kod mu{karaca i `ena u odnosu na njihovu starost. Ispitano je 19 mu{karaca (YM) i 19 `ena (YW) starosti 25-32 godine, kao i 11 mu{karaca (OM) i 11 ena (OW) starosti 63-71 godine, koji su svi bili neaktivni. Odre|eni su slede}i faktori: aktivnost superoksid dismutaze (SOD), glutation-reduktaze (GR), glutation-peroksidaze (GPX), katalaze (CAT), ukupni antioksidantni status (TAS) u eritrocitima, kao i retinol, alfa-tokoferol, mokra}n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…There was also no signifi cant difference in TAC values between male and female dogs. Most of the studies in healthy humans showed a signifi cant decline of TAC levels with age [20,[46][47][48]. Moreover, signifi cantly lower TAC values were found in older men than in young men, but no such difference was found in women [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…There was also no signifi cant difference in TAC values between male and female dogs. Most of the studies in healthy humans showed a signifi cant decline of TAC levels with age [20,[46][47][48]. Moreover, signifi cantly lower TAC values were found in older men than in young men, but no such difference was found in women [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…Additional support for this notion is provided by observations showing that MPTP and NOS2 induction synergistically promote degeneration of dopaminergic neurons in culture (47). Thus, S-nitrosylation and inactivation of parkin by NO may contribute to pathogenesis of Parkinson's disease by preventing the degradation of parkin substrates, which accumulation triggers neurodegeneration (48,49).…”
Section: S-nitrosylation Inmentioning
confidence: 77%
“…Increased iron content in circulation and tissues contributes to the generation of free radicals through the Fenton reaction. Under such conditions, it is likely that Cp ferroxidase activity upregulates to handle the increased availability of ferrous iron, thus enhancing the efflux of ferric iron from stores and accelerating its uptake by transferrin in the circulation (23,24,37).…”
Section: Discussionmentioning
confidence: 99%